Optimization of the event timetable scheduling problem with user preferences - Kong, Jin Wern Justin (2017)
Event timetable scheduling is a process which involves planning and coordination between multiple individuals to determine a suitable time to organise an event. This usually involves a lengthy process of exchanging correspondence between individuals until a suitable time is agreed upon. This study aims to improve the event timetable scheduling process by developing an Android application to make scheduling events an easier task for users. The application creates an online poll using Google Sheets where users can specify their event date and time preferences. A simulated annealing optimisation algorithm is then used to generate an event schedule based on these user’s preferences. The completed application was evaluated by a number of users who agreed that the application was helpful although more work could be done to improve the user interface of the application.